Improving Knowledge of Family Nutrition Fulfillment as an Effort to Prevent Congenital Disorders in Couples of Reproductive Age in Rambipuji District, Jember - Elfiah, Ulfa; Shinta Rumastika, Nindya; Surya Wahyudi, Septa; Krisno Adji, Novan; Aisyah Amini, Stefia; Faa'is Artama, Alfila; Nadiyatul Husna, Fella; Sahazra Chakra Firdaussaid, Jihad; Nur Hidayah, Siti (Pascasarjana Universitas Mataram, 2025)
The global prevalence of congenital defect reaches 0.992 per 1,000 live births, with a high incidence rate also observed in Jember Regency, particularly in Rambipuji District. Nutrition intake, including protein, is essential to prevent congenital defect, but many sufferers come from families with poor nutritional intake. To prevent congenital defect through education and assistance in planting healthy crops for family nutrition and mapping cases in Jember Regency as a promotive and preventive measure. This study design is a quasi-experimental using pretest and posttest. Participants consisted of 30 married couples aged 14-49 years. The intervention included two educational sessions on congenital defect and the management of healthy crops to be processed into nutritious food. A healthy food recipe book was provided, followed by a cooking demonstration by each participant. The knowledge of couples of reproductive ages increased from pretest to posttest with an average increase of 22.5. Statistical analysis using Wilcoxon showed a significant difference in the knowledge of couples of reproductive ages after the intervention (p=0.000). Providing education and training effectively increases knowledge and skills in managing food for family nutrition among couples of reproductive ages. Similar studies with a larger population can be conducted to review the effectiveness more comprehensively.